Hydrogeology: Quo vadis…? A survey on the future of hydrogeology and seven ways forward in the light of global challenges - Christian Moeck; Olga Darazs; Andreas Ebert; Jannis Epting; Marie-José Gilbert; Sophie Gschwind; Jakob Helbing; Daniel Hunkeler; Pierre Yves Jeannin; Joaquin Jimenez-Martinez; Flavio Malaguerra; Lawrence Och; et al. (Hydrogeology Journal, 2026)

Triple oxygen isotope signatures of cherts record pore-fluid composition and temperature across the opal-CT to quartz transition - Oskar Schramm; Katharina Ebert; Patrick J. Frings; Andreas Pack; Tommaso Di Rocco; Volker Karius; Nils Keno Lünsdorf; Dieter Korn; Daniel Herwartz; Michael Tatzel (Earth and Planetary Science Letters, 2026)

Toxicokinetics of homosalate in humans after dermal application: applicability of oral-route data for exposure assessment by human biomonitoring - Katharina E. Ebert; Peter Griem; Tobias Weiss; Thomas Brüning; Heiko Hayen; Holger M. Koch; Daniel Bury (Archives of Toxicology, 2024)
Homosalate (HMS) is a UV filter used in sunscreens and personal care products as a mixture of cis - and trans -isomers. Systemic absorption after sunscreen use has been demonstrated in humans, and concerns have been raised about possible endocrine activity of HMS, making a general population exposure assessment desirable. In a previous study, it was shown that the oral bioavailability of cis -HMS ( c HMS) is lower than that of trans -HMS ( t HMS) by a factor of 10, calling for a separate evaluation of both isomers in exposure and risk assessment. The aim of the current study is the investigation of HMS toxicokinetics after dermal exposure. Four volunteers applied a commercial sunscreen containing 10% HMS to their whole body under regular-use conditions (18–40 mg HMS (kg bw) −1 ). Parent HMS isomers and hydroxylated and carboxylic acid metabolites were quantified using authentic standards and isotope dilution analysis. Further metabolites were investigated semi-quantitatively. Elimination was delayed and slower compared to the oral route, and terminal elimination half-times were around 24 h. After dermal exposure, the bioavailability of c HMS was a factor of 2 lower than that of t HMS. However, metabolite ratios in relation to the respective parent isomer were very similar to the oral route, supporting the applicability of the oral-route urinary excretion fractions for dermal-route exposure assessments. Exemplary calculations of intake doses showed margins of safety between 11 and 92 (depending on the approach) after single whole-body sunscreen application. Human biomonitoring can reliably quantify oral and dermal HMS exposures and support the monitoring of exposure reduction measures.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Troubled waters: Threats and extinction risk of the sharks, rays and chimaeras of the Arabian Sea and adjacent waters - Rima W. Jabado; Peter M. Kyne; Riley A. Pollom; David A. Ebert; Colin A. Simpfendorfer; Gina M. Ralph; Shaikha S. Al Dhaheri; K. V. Akhilesh; Khadeeja Ali; Mohamud Hassan Ali; Tariq M. S. Al Mamari; K. K. Bineesh; et al. (Fish and Fisheries, 2018)
The extinction risk of sharks, rays and chimaeras is higher than that for most other vertebrates due to low intrinsic population growth rates of many species and the fishing intensity they face. The Arabian Sea and adjacent waters border some of the most important chondrichthyan fishing and trading nations globally, yet there has been no previous attempt to assess the conservation status of species occurring here. Using IUCN Red List of Threatened Species Categories and Criteria and their guidelines for application at the regional level, we present the first assessment of extinction risk for 153 species of sharks, rays and chimaeras. Results indicate that this region, home to 15% of described chondrichthyans including 30 endemic species, has some of the most threatened chondrichthyan populations in the world. Seventy‐eight species (50.9%) were assessed as threatened (Critically Endangered, Endangered or Vulnerable), and 27 species (17.6%) as Near Threatened. Twenty‐nine species (19%) were Data Deficient with insufficient information to assess their status. Chondrichthyan populations have significantly declined due to largely uncontrolled and unregulated fisheries combined with habitat degradation. Further, there is limited political will and national and regional capacities to assess, manage, conserve or rebuild stocks. Outside the few deepsea locations that are lightly exploited, the prognosis for the recovery of most species is poor in the near‐absence of management. Concerted national and regional management measures are urgently needed to ensure extinctions are avoided, the sustainability of more productive species is secured, and to avoid the continued thinning of the regional food security portfolio.

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Hydrogeologische Untersuchungen im oberflächennahen Opalinuston (Bohrloch Lausen, Schweiz) - Tobias Vogt; Uwe Hekel; Andreas Ebert; Jens K. Becker; Daniel Traber; Silvio Giger; Monika Brod; Christian Häring (Grundwasser, 2017)

Reassessment of GLUT7 and GLUT9 as Putative Fructose and Glucose Transporters - Karolin Ebert; Maren Ludwig; Kerstin Elisabeth Geillinger; Gina Catalina Schoberth; Jasmin Essenwanger; Jürgen Stolz; Hannelore Daniel; Heiko Witt (The Journal of Membrane Biology, 2017)

Adaptation with gene flow across the landscape in a dune sunflower - ROSE L. ANDREW; KATHERINE L. OSTEVIK; DANIEL P. EBERT; LOREN H. RIESEBERG (Molecular Ecology, 2012)
Isolation by adaptation increases divergence at neutral loci when natural selection against immigrants reduces the rate of gene flow between different habitats. This can occur early in the process of adaptive divergence and is a key feature of ecological speciation. Despite the ability of isolation by distance (IBD) and other forms of landscape resistance to produce similar patterns of neutral divergence within species, few studies have used landscape genetics to control for these other forces. We have studied the divergence of Helianthus petiolaris ecotypes living in active sand dunes and adjacent non‐dune habitat, using landscape genetics approaches, such as circuit theory and multiple regression of distance matrices, in addition to coalescent modelling. Divergence between habitats was significant, but not strong, and was shaped by IBD. We expected that increased resistance owing to patchy and unfavourable habitat in the dunes would contribute to divergence. Instead, we found that landscape resistance models with lower resistance in the dunes performed well as predictors of genetic distances among subpopulations. Nevertheless, habitat class remained a strong predictor of genetic distance when controlling for isolation by resistance and IBD. We also measured environmental variables at each site and confirmed that specific variables, especially soil nitrogen and vegetation cover, explained a greater proportion of variance in genetic distance than did landscape or the habitat classification alone. Asymmetry in effective population sizes and numbers of migrants per generation was detected using coalescent modelling with Bayesian inference, which is consistent with incipient ecological speciation being driven by the dune habitat.

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

Twelve microsatellite markers in the invasive tunicate, Didemnum vexillum, isolated from low genome coverage 454 pyrosequencing reads - Cathryn L. Abbott; Daniel Ebert; Amy Tabata; Thomas W. Therriault (Conservation Genetics Resources, 2011)

Rhodopsin population genetics and local adaptation: variable dim‐light vision in sand gobies is illuminated - DANIEL EBERT; ROSE L. ANDREW (Molecular Ecology, 2009)
The visual pigments of fish are thought to be adapted to the variable spectral qualities of aquatic light environments. Most research on the role of natural selection on the evolution of rhodopsins and dim‐light vision in fish has focused on variation among species and higher taxa. In this issue, Larmuseau et al. reveal substantial intraspecific sequence variation in RH1 (the rhodopsin gene) in sand gobies ( Pomatoschistus minutus ). Using population genetics and molecular evolution approaches, they detect positive selection on RH1 and find evidence for adaptation to local light conditions.

Multi-scale landscape factors influencing stream water quality in the state of Oregon - Maliha S. Nash; Daniel T. Heggem; Donald Ebert; Timothy G. Wade; Robert K. Hall (Environmental Monitoring and Assessment, 2009)

Stocking impact and migration pattern in an anadromous brown trout ( Salmo trutta ) complex: where have all the stocked spawning sea trout gone? - Daniel E. Ruzzante; Michael M. Hansen; Dorte Meldrup; Kaare M. Ebert (Molecular Ecology, 2004)
We examined polymorphism at seven microsatellite loci among sea trout ( Salmo trutta ) ( n = 846) collected from three areas in the Limfjord (Denmark). We then assessed their potential population source by comparing, using a mixed stock analysis (MSA) Bayesian framework, their genetic composition to that of brown trout collected from 32 tributaries pooled into nine geographical regions ( n = 3801) and two hatcheries ( n = 222) used for stocking. For each of the three regional sea trout groups (western, central and eastern Limfjord, n = 91, n = 426, n = 329, respectively), MSA was conducted with (i) all individuals in the group, (ii) with the subset of spawning sea trout only and (iii) with the subset of foraging, nonspawning individuals only, a subset that consisted primarily of sea trout caught during their first year at sea. For all three regional sea trout groups, a higher proportion of individuals (regardless of whether they were foraging or spawning) appear to have originated from the rivers that drain locally, than from the rivers that drain in other parts of the Limfjord. This suggests (1) that sea trout, at least during their first year at sea, undertake limited migrations within the Limfjord system and (2) that sea trout on their spawning run were caught close to their natal rivers. The proportion of sea trout of hatchery origin varied widely among all three Limfjord areas and broadly reflected regional stocking histories, with high proportions of sea trout of domestic origin in the east (39.3%), where stocking with domestic trout was practised intensely at the time of sampling, and in the west (57.2%), where a programme of coastal stocking of post smolts took place over several years in the early 1990s. In contrast, in the central Limfjord, where stocking with domestic trout was largely abandoned in the early 1990s, the proportion of sea trout of domestic origin was only 8.5%. Interestingly, for all three regional sea trout groups, virtually no sea trout of hatchery origin were found among the spawning individuals, which were on average larger than the nonspawning sea trout. These results suggest that stocked domestic brown trout that become anadromous experience high mortality at sea and are therefore largely absent among the larger, spawning individuals. We conclude that sea trout of domestic origin exhibit much reduced ability to reproduce and are unlikely to contribute significantly to the local gene pool largely because of a relatively high mortality at sea before the onset of maturity.

Comparative genetic study confirms exceptionally low genetic variation in the ancient and endangered relictual conifer, Wollemia nobilis (Araucariaceae) - Rod Peakall; Daniel Ebert; Leon J. Scott; Patricia F. Meagher; Cathy A. Offord (Molecular Ecology, 2003)
The Wollemi pine, Wollemia nobilis (Araucariaceae), was discovered in 1994 as the only extant member of the genus, previously known only from the fossil record. With fewer than 100 trees known from an inaccessible canyon in southeastern Australia, it is one of the most endangered tree species in the world. We conducted a comparative population genetic survey at allozyme, amplified fragment length polymorphism (AFLP) and simple sequence repeat (SSR) loci in W. nobilis , Araucaria cunninghamii and Agathis robusta — representatives of the two sister genera. No polymorphism was detected at 13 allozyme loci, more than 800 AFLP loci or the 20 SSR loci screened in W. nobilis . In Ag. robusta only one of 12 allozyme loci, five of 800 AFLP loci and none of the 15 SSR loci were variable. For A. cunninghamii , 10 of > 800 AFLP loci and five of 20 SSR loci were variable. Thus low genetic diversity characterizes all three species. While not ruling out the existence of genetic variation, we conclude that genetic diversity is exceptionally low in the Wollemi pine. To our knowledge this is the most extreme case known in plants. We conclude that the combination of small population effects, clonality and below‐average genetic variation in the family are probable contributing factors to the low diversity. The exceptionally low genetic diversity of the Wollemi pine, combined with its known susceptibility to exotic fungal pathogens, reinforces current management policies of strict control of access to the pines and secrecy of the pine locations.

Assessing Landscape Condition Relative to Water Resources in the Western United States: A Strategic Approach - K. Bruce Jones; Daniel T. Heggem; Timothy G. Wade; Anne C. Neale; Donald W. Ebert; Maliha S. Nash; Megan H. Mehaffey; Karl A. Hermann; Anthony R. Selle; Scott Augustine; Iris A. Goodman; Joel Pedersen; et al. (Environmental Monitoring and Assessment, 2000)